443 Intravenous fluid assessment and prescribing in general paediatrics. (17th August 2022) - Francis, Sunil
Abstract : Aims: Intravenous (IV) fluid prescription errors in paediatrics have increased in our department over the last 12 months leading to this becoming a Patient Safety Incident Response Framework priority for the department. As part of a wider quality improvement effort, a project was devised to target rotational junior doctors (FY1-ST3 level) to address their contribution to errors in fluids at the Derbyshire Children's Hospital. The aim of this project was to increase knowledge and confidence in junior doctors' ability to assess and prescribe IV fluids. Methods: Baseline knowledge and confidence data was collected from 71% of eligible doctors finding mean confidence of 2.1 in a likert scale of 1-4. Knowledge deficits were tested on a quiz, identifying: indication, route of administration, assessment parameters, volumes to administer and calculations. PDSA cycles were developed to test change ideas. Results: PDSA 1: A structured teaching program was developed to address the deficits was delivered to eligible doctors and resources made available to those who were unable to attend in person. Data after 4 months found an increase in confidence to 3.2 (1.1 point increase) and generally increased knowledge. PDSA 2: Specific deficits were still identified after the delivery of the structured teaching, including capping IV fluid volumes and volumes for shock boluses. A 'Top Tips' poster was developed to aid with fluid assessment and prescribing, but was delayed due to RSV surge. Regardless, confidence measures were relatively maintained (score of 3). Conclusion: IV fluid assessment and prescribing are complex tasks for novices in paediatrics. Training is required to address this, and has been found to consistently improve the confidence in prescribers. Competence also seems to improve with education but more work is needed to help prescribers from day 1 of their clinical attachments and to remedy specific issues in fluid assessment and prescribing.